New ELISAs with high specificity for soluble oligomers of amyloid β-protein detect natural Aβ oligomers in human brain but not CSF - Yang, Ting (2013)
BACKGROUND: Soluble oligomers of amyloid β-protein (Aβ) have been increasingly linked to synaptic dysfunction, tau alteration and neuritic dystrophy in Alzheimer’s disease (AD) and mouse models. There is a great need for assays that quantify Aβ oligomers with high specificity and sensitivity. METHODS: We designed and validated two oligomer-specific (o-) ELISAs using either an Aβ aggregate-selective monoclonal for capture and a monoclonal to the free N-terminus for detection or the latter antibody for both capture and detection. RESULTS: The o-ELISAs specifically quantified pure oligomers of synthetic Aβ with sizes from dimers up to much larger assemblies and over a wide dynamic range of concentrations, whereas Aβ monomers were undetectable. Natural Aβ oligomers of similarly wide size and concentration ranges were measured in extracts of AD and control brains, revealing >1,000-fold higher concentrations of Aβ oligomers than monomers in the soluble fraction of AD cortex. The assays quantified the age-related rise in oligomers in hAPP transgenic mice. Unexpectedly, none of 90 human CSF samples gave a specific signal in either o-ELISA. CONCLUSIONS: These new o-ELISAs with rigorously confirmed specificity can quantify oligomer burden in human and mouse brains for diagnostic and mechanistic studies and for AD biomarker development. However, our data raise the likelihood that the hydrophobicity of Aβ oligomers makes them very low or absent in aqueous CSF.